Preoperative Prediction Power of Radiomics for Breast Cancer: A Systemic Review and Meta-Analysis - Li, Zhenkai; Ye, Juan; Du, Hongdi; Cao, Ying; Wang, Ying; Liu, Desen; Zhu, Feng; Shen, Hailin (Frontiers in Oncology, 2022)
Background: To evaluate the preoperative predictive value of radiomics in the diagnosis of breast cancer (BC). Methods: By searching PubMed and Embase libraries, our study identified 19 eligible studies. We conducted a meta-analysis to assess the differential value in the preoperative assessment of BC using radiomics methods. Results: Nineteen radiomics studies focusing on the diagnostic efficacy of BC and involving 5865 patients were enrolled. The integrated sensitivity and specificity were 0.84 (95% CI: 0.80–0.87, I2 =76.44%) and 0.83 (95% CI: 0.78–0.87, I2 =81.79%), respectively. The AUC based on the SROC curve was 0.91, indicating a high diagnostic value. Conclusion: Radiomics has shown excellent diagnostic performance in the preoperative prediction of BC and is expected to be a promising method in clinical practice.